2020
DOI: 10.3389/fonc.2020.592796
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery With Concurrent Immunotherapy in Melanoma Brain Metastases Is Feasible and Effective

Abstract: Objective: Stereotactic radiosurgery (SRS) is an established treatment for brain metastases in the management of metastasized melanoma. The increasing use of checkpoint inhibitors in melanoma therapy leads to combined treatment schemes consisting of immunotherapy and SRS that need to be evaluated regarding safety and feasibility. Methods: We retrospectively analyzed 36 patients suffering from cerebral metastasized melanoma. Between November 2011 and May 2016, altogether 66 brain metastases were treated with si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…Prior observational studies have demonstrated concurrent SRS-IT associated with more effective local control and OS for melanoma BM (Table 5). [11][12][13][14][15][16][26][27][28][33][34][35] Our analysis reiterates the synergistic response of SRS-IT but also further strengthens this relationship by performing additional multivariate analyses of individual BM, patient, treatment and clinical factors that have been previously lacking in the literature. We also present for the first time, outcomes after SRS in patients with melanoma BM according to RANO-BM criteria which may be useful when comparing to cohorts at other institutions and for future trial planning.…”
Section: Discussionsupporting
confidence: 68%
“…Prior observational studies have demonstrated concurrent SRS-IT associated with more effective local control and OS for melanoma BM (Table 5). [11][12][13][14][15][16][26][27][28][33][34][35] Our analysis reiterates the synergistic response of SRS-IT but also further strengthens this relationship by performing additional multivariate analyses of individual BM, patient, treatment and clinical factors that have been previously lacking in the literature. We also present for the first time, outcomes after SRS in patients with melanoma BM according to RANO-BM criteria which may be useful when comparing to cohorts at other institutions and for future trial planning.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, multimodality techniques appear to provide the greatest survival benefits, as retrospective evidence supports the combination of ICI in conjunction with SRS therapy for which clinical trials involving radiation combined with ICI (ClinicalTrials.gov identifier: NCT03340129) and targeted therapies (Clin-icalTrials.gov identifier: NCT02974803) are ongoing. 123,124…”
Section: Advanced Metastatic Diseasementioning
confidence: 99%
“…SRS in combination with immunotherapy has shown better clinical outcomes versus SRS or IT alone ( Fig. 3 ) [ 8 10 , 38 , 50 , 51 ]. A study found that the median OS in patients treated with SRS + IT was 15.77 months, significantly improved from the historical median OS [ 46 ].…”
Section: Immunotherapy In Melanoma Brain Metastasesmentioning
confidence: 99%
“…One such field of therapy that has gained widespread attention in the past 10 years has been immunotherapy (IT). IT has shown promising results in improving the overall survival (OS) rate in patients with BrM, both alone and in combination with traditional therapies [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%